Professor John O’M. Bockris 1923–2013 - Storms, Edmund (Journal of Scientific Exploration, 2014)
Bernhardt Patrick John O’Mara Bockris arrived on January 5, 1923, in Johannesburg, South Africa, and left on July 7, 2013, in Florida after spending 90 years on this planet. In between these events, he explored this world with intensity, courage, and creativity. He sought education at Brighton Technology College and obtained his Ph.D. from the Imperial College of Science and Technology in England. Later, the University of London awarded him the additional distinction of a D.Sc. degree. With these tools in hand, he went on to become one of the world’s experts in Electrochemistry and taught many students most of what they know about the subject through his lectures, many papers, and books. Much of this pioneering work was done while he taught at the Imperial College in London (1945–1953), at the University of Pennsylvania (1953–1972), and with a short stay at Flinders University in South Australia (1972–1978). As a result, he was awarded much recognition for his contribution to this growing, but conventional science, and is now considered the father of modern electrochemistry. But then John crossed a forbidden boundary when in 1989, while teaching at the University of Texas in College Station, he started a study of what is called cold fusion—but first some background.